2015
DOI: 10.1371/journal.pone.0134342
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Opacity Proteins Interferes with the Transmigration of Neisseria gonorrhoeae across Polarized Epithelial Cells

Abstract: Neisseria gonorrhoeae (GC) establishes infection at the mucosal surface of the human genital tract, most of which is lined with polarized epithelial cells. GC can cause localized as well as disseminated infections, leading to various complications. GC constantly change their surface structures via phase and antigenic variation, which has been implicated as a means for GC to establish infection at various anatomic locations of male and female genital tracks. However, the exact contribution of each surface molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…To address the potential role of mAb 2C7-dependent complement activation in facilitating opsonophagocytosis of the 3-Hex/G+ mutant, we recreated the 3-Hex/G+ LOS structure in the background of an Opa-negative MS11 strain (42). The 3-Hex/G+ Opa-negative MS11 mutant strain bound similar (low) levels of mAb 2C7 and was fully resistant (>100% survival) to killing by 4 μg/ml of mAb 2C7 plus 20% complement (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address the potential role of mAb 2C7-dependent complement activation in facilitating opsonophagocytosis of the 3-Hex/G+ mutant, we recreated the 3-Hex/G+ LOS structure in the background of an Opa-negative MS11 strain (42). The 3-Hex/G+ Opa-negative MS11 mutant strain bound similar (low) levels of mAb 2C7 and was fully resistant (>100% survival) to killing by 4 μg/ml of mAb 2C7 plus 20% complement (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GC aggregation and adherence to host cells through these molecules may influence each other, therefore changing both the infectivity and antibiotic resistance of GC in the reproductive tract of women. Indeed, we have previously shown that Opa expression facilitates GC adherence to host cells and GC aggregation, but reduces GC penetration into both polarized epithelial cell monolayers and the endocervical epithelium in the tissue explant model [ 16 , 20 ]. The functions of Opa in both GC-GC and GC-epithelial interactions enable Opa-expressing GC to survive better in the presence of antibiotic agents and dominate the colonization of the epithelial surface.…”
Section: Discussionmentioning
confidence: 99%
“…The GC biofilm progresses from an intimately associated aggregation of microcolonies to an organized biofilm. Pili, opacity-associated protein (Opa), and lipooligosaccharides (LOS), three well-characterized phase variable surface molecules of GC, have been shown to mediate inter-bacterium interactions to form aggregates [ 15 , 16 , 17 ]. How phase variations in their expression contribute to different GC-GC interactions and whether these interactions affect GC susceptibility to antibiotics is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we created a mutant in the parent (or wild-type [WT]) strain MS11 4/3/1, where only lgtG was locked on to create WT/Gϩ; the ability of HepI glycans to phase vary was unaffected in this mutant. As previously described (15), a 3-Hex/Gϩ LOS mutant was made in the background of MS11 ΔOpa for opsonic killing studies by PMNs, where all 11 opa genes were deleted (16).…”
Section: Methodsmentioning
confidence: 99%
“…where all 11 Opa proteins had been deleted (MS11 ΔOpa) (15,16). Elimination of Opa(s) avoids interactions with CEACAM3 on human PMNs that would result in nonopsonic killing (17,18) and thereby confound interpretation of results.…”
Section: -Hex/g؉ Opsonized With 2c7-ximab(s) Is Killed By Pmns In a mentioning
confidence: 99%